Ultrasonographic Evaluation of Glycemic Control Effect on Placental Vascularization in Pregnancy with Type 1 Diabetes Mellitus - Kozinszky, Zoltan; Altorjay, AbelT.; Molnar, Andras; Nyári, Tibor; Vari, Sandor G.; Nemeth, Gabor; Suranyi, Andrea (Experimental and Clinical Endocrinology & Diabetes, 2019)
Aims The aim of our study was to assess the effect of glycemic control on placental vascularization in pregnancies complicated by type 1 diabetes mellitus (T1DM) and to compare dataset of optimal/suboptimal glycemic control to normal placental 3-dimensional power Doppler (3-DPD) indices in 2nd and 3rd trimester.Methods Placental vascularization of pregnant women was prospectively evaluated by 3-DPD ((vascularization-index (VI); flow-index (FI); vascularization-flow-index (VFI)) ultrasound technique. The normal pregnancies (n=214) were compared to those complicated by T1DM (n=53) with optimal (HbA1C≤6%;≤ 42 mmol/mol) and suboptimal (HbA1C>6%;>42 mmol/mol) glycemic control.Results Pregnancies complicated by T1DM expressed lower placental vascularization indices as compared with normal pregnancies (adjusted odds ratio (AOR) for VI:0.86; FI:0.94; VFI:0.76). Placental 3-DPD indices have a significant correlation with HbA1C and optimal glycemic control is associated with lower placental perfusion (AOR for VI:1.64; FI:1.13; VFI:2.34). Short-term adverse neonatal outcome was predicted by lower 3-DPD indices (AORVI:0.83, AORFI:0.93, AORVFI:0.66, p<0.05 for each index). Besides the glycemic control, the pregestational body mass index (BMI), had significant influences on placental perfusion.Conclusions VI displayed the best screening ability for suboptimal glycemic control with a sensitivity of 90.9%. The suboptimal glycemic control has a direct deteriorating effect on placental vasculature. Therefore the ultrasound examination could be an adjunct diagnostic modality for pregnant women with T1DM.
Keywords: glycemic control; placental vascularization; type 1 diabetes mellitus; 3-dimensional power Doppler indices; ultrasound